Maternity and Child Welfare
1928 1928 1920s 5 pages WEST RIDING COUNTY COUNCIL - PUBLIC HEALTH DEPARTMENT. MATERNITY AND CHILD WELFARE. The County Scheme for Maternity and Child Welfare deals with arrangements for attending to the health of expectant and nursing mothers, and of children under 5 years of age. 20,000 Notifications of births are distributed to the Nurses annually. The following are the numbers of visits paid by Health Visitors during 1926:- To expectant mothers 8,924. To Infants under 1 year 168,427. To children 1 to 5 years of age 50,684. Special visits (Ophthalmia neonatorum, 4,631. teething, feeding, &c.) Measles 1,364. In the County Notification of Births area, the staff employed includes :- 2 Asst. Inspectors of Nurses and Midwifes. 101 Whole-time Health Visitors and School Nurses. 65 Part-time Health Visitors and School Nurses. Ninety-six Maternity and Child Welfare Centres are now established in the County. The Centres are usually open one afternoon a week, with a doctor and nurse in attendance. During 1926, 140,283 mothers and 141,992 children attended at the Centres, and during the same period 1,286 expectant mothers and 12,091 children attended a Centre for the first time. In addition to the above service, no effort has been spared to maintain and improve other branches of this work, e.g. utilisation of Maternity Hospitals, Treatment of Puerperal Fever and Ophthalmia Neonatorum, Convalescent Treatment for mothers after difficult confinement; Hospital and Convalescent Treatment for children up to 5 years of age; provision of midwives in necessitous cases; supply of trained midwives in non-provided areas; formation of Nursing Associations; provision of Dried Milk in necessitous cases. Much attention has been paid to Maternal Mortality in the provision and extension of:- (a) Maternity Homes. Arrangements have been made for the admission of West Riding patients into 15 Maternity Homes. In 1926, 484 patients were admitted under the County Scheme. Of this number, 308 patients paid the fees direct to the Hospital; in the remaining 176 cases, the County Council paid a sum of £1,382.12.4 to the hospitals concerned and of this amount, a sum of £446.15.7. was recoverable. (b) Treatment of Puerperal Fever. The County Council have agreements with 11 Hospitals for the admission of women suffering from Puerperal Fever or Puerperal Pyrexia, and have also arrangements to provide domiciliary nursing at the request of the Medical Practitioner P.T.O. 292/824/1/120